Reactive arthritis after vaccination against SARS-CoV-2: A case series and a mini-review. Issue 1 (31st December 2023) - Wojturska, Wiktoria; Nowakowski, Jarosław; Pilch, Weronika; Biernikowicz, Małgorzata; Korkosz, Mariusz
ABSTRACT: The rapid development of COVID-19 vaccines became essential for addressing the global pandemic. Reactive arthritis after vaccination has been a rare phenomenon. Here, we present a case series of three patients with joint inflammation possibly attributed to COVID-19 immunization (mRNA and live adenovirus vectored vaccine). Symptoms were alleviated using non-steroid anti-inflammatory drugs and glucocorticoids. After follow-up, the patients have not been diagnosed with any other rheumatic disease. Reactive arthritis after the COVID-19 vaccine is an unusual adverse effect and poses a negligible risk in comparison to the benefits of immunization, but it should be considered in differential diagnostics by a practicing rheumatologist who cares for patients with new-onset arthritis without apparent cause at the time of pandemic.